Spirende professionelle: Et indblik i studerendes professionsidentitetsdannelse i praksisforløb - Johansson, Nicolaj; Bundgaard, Stine Bylin (Tidsskrift for Professionsstudier, 2023)
Society’s complexity and constant movement place great demands on education programs to train competent, reflexive, robust and committed students who can think, act and act in a qualified and professional manner. In this article, we will examine the students’ experience of professional identity formation during practicum. Educating into a profession and developing a professional identity is a transition that contains many complex facets in the form of developing expert knowledge, skills, behavior, attitudes, and professionalism (Wilson et al., 2013). Barnet (2012) describes this transition as a dynamic journey without a specific destination, which is influenced by both the individual’s personal characteristics and the professional practice that the individual participates in. The starting point is impact in practice courses on the Social Education and the Medical Education, where social identities is articulated and the formation of professional identity is the focal point (Rothuizen, 2015; Van den Broek et al., 2020; Rothuizen & Togsverd, 2020a). Based on an analysis of field studies and focus group interviews with students, an argument is made for understanding the concept as social identity based on the general picture drawn from the data. The understanding of social identity contains adjustment of the self in relation to the profession and the exercise thereof (action). Knowledge that is essential in the debate about how professions are trained for a complex and changing world.